Study on milk composition of Mehsana goat at organized farm - KP Singh; JB Patel; HH Panchasara; RR Shah; SM Patel (Journal of Livestock Biodiversity, 2025)
One thousand nine hundred sixty one milk samples of Mehsana goats maintained at Livestock Research Station, SDAU, Sardarkrushinagar, Gujarat, were analyzed to study the goat milk composition during the year 2006 and 2007. The data was grouped according to year, seasons and months. The overall means ± SE for fat, SNF, protein and lactose contents were observed 2.91 ± 0.02, 8.29 ± 0.01, 2.82 +0.05 and 4.78 ± 1.53 percent, respectively. Higher milk constituents were observed in 2006 for fat (3.05 ± 0.32%), SNF (10.89 ± 3.01%), protein (3.03 ± 0.09%) and Lactose (6.34 ± 1.52%). The corresponding lower estimates for the year 2007 were: 2.89 ± 0.03, 7.87 ± 0.01, 2.81 ± 0.01 and 4.52 ± 0.01 percent, respectively. The milk constituents were observed higher in winter season for SNF (9.06 ± 0.08%) and lactose (5.57 ± 1.11%), whereas, in autumn season high estimates were estimated for fat (3.53 ± 0.12%) and protein contents (3.06 ± 0.02%). The goat milk constituents revealed higher means in the month of October for fat (5.38 ± 0.43%), SNF (8.84 ± 0.18%) and protein (3.45 ± 0.06%), but lactose content was high in December month (6.76 ± 2.3 8%). The present study revealed higher fat, SNF, protein and lactose constituents in goat milk during initial stage of lactation (autumn and winter seasons) and lower estimates in summer season (last stage of lactation).